Persistent Luminescence in Strontium Aluminate: A Roadmap to a Brighter Future. (30th October 2022) - Van der Heggen, David; Joos, Jonas J.; Feng, Ang; Fritz, Verena; Delgado, Teresa; Gartmann, Nando; Walfort, Bernhard; Rytz, Daniel; Hagemann, Hans; Poelman, Dirk; Viana, Bruno; Smet, Philippe F.
Abstract: Glow‐in‐the‐dark materials have been around for a long time. While formerly materials had to be mixed with radioactive elements to achieve a sufficiently long and bright afterglow, these have now been replaced by much safer alternatives. Notably strontium aluminate, SrAl2 O4, doped with europium and dysprosium, has been discovered over two decades ago and since then the phosphor has transcended its popular use in watch dials, safety signage, or toys with more niche applications such as stress sensing, photocatalysis, medical imaging, or flicker‐free light‐emitting diodes. A lot of research efforts are focused on further improving the storage capacity of SrAl2 O4 :Eu 2+, Dy 3+, including in nanosized particles, and on finding the underlying physical mechanism to fully explain the afterglow in this material and related compounds. Here an overview of the most important results from the research on SrAl2 O4 :Eu 2+, Dy 3+ is presented and different models and the underlying physics are discussed to explain the trapping mechanism at play in these materials. Abstract : Glow‐in‐the‐dark luminescent materials hold potential for a wide range of applications. Starting with the discovery of the green‐emitting SrAl2 O4 :Eu 2+, Dy 3+ in the 1990s, the key experiments and insights that led to the current understanding of the energy storage mechanism, which is transferable to several other materials, are discussed. The remaining challenges and future applications are also discussed.